2019
DOI: 10.3171/2018.8.spine171328
|View full text |Cite
|
Sign up to set email alerts
|

Unintended facet fusions after Dynesys dynamic stabilization in patients with spondylolisthesis

Abstract: OBJECTIVEThe pedicle screw–based Dynesys dynamic stabilization (DDS) has reportedly become a surgical option for lumbar spondylosis and spondylolisthesis. However, it is still unclear whether the dynamic construct remains mobile or eventually fuses. The aim of this study was to investigate the incidence of unintended facet arthrodesis after DDS and its association with spondylolisthesis.METHODSThis retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Reports have described bone facet regrowth and unintended facet arthrodesis after lumbar decompression and lumbar dynamic stabilization surgery [16][17][18][19][20][21] . Dohzono et al 16) evaluated bone regrowth at facet joints 2 years after microendoscopic lumbar decompression surgery and reported a significant correlation between bone regrowth and percentage slippage in lumbar spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports have described bone facet regrowth and unintended facet arthrodesis after lumbar decompression and lumbar dynamic stabilization surgery [16][17][18][19][20][21] . Dohzono et al 16) evaluated bone regrowth at facet joints 2 years after microendoscopic lumbar decompression surgery and reported a significant correlation between bone regrowth and percentage slippage in lumbar spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Kanayama et al 18,19) reported that facet fusion occurred in 12 of 64 patients (18.8%) and 14 of 43 patients (32.6%) by an average of 59.5 months and 82 months, respectively, after posterior lumbar dynamic stabilization surgery using the Graf artificial ligament. Fay et al 21) reported that unintended facet fusion occurred in 52.1% of patients 4 years after Dynesys dynamic stabilization. Furthermore, Fay et al 21) reported that facet fusion was significantly greater in patients with lumbar spondylolisthesis and those over the age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual goal for preservation of segmental mobility and reduction of ASD in DDS remained equivocal. 14,15,17,18,32 Despite the fact that DDS is designed to stabilize the spine while allowing controlled motion, limited motion at the instrumented level of the lumbar spine has been reported, which can cause an overload of the adjacent segments and result in ASD. In the review study, 3.7% (0%-8.4%) of patients underwent secondary reoperation due to ASD, which was lower than fusion surgery (13%).…”
Section: Figmentioning
confidence: 99%
“…Pedicle screw-based dynamic stabilization has been reported as an effective and viable option in surgical management of lumbar spondylosis. [13][14][15][16][17][18] As opposed to fusion, the most commonly raised question regarding these screws, which do not aim to fuse the spine, is their risk of loosening. This risk in pedicle screw-based dynamic stabilization has reportedly been approximately 5% per screw and 20% per patient in 2-5 years postoperatively.…”
mentioning
confidence: 99%